Sluthilsener i franske forretningsbreve - Hermann, Helle (HERMES - Journal of Language and Communication in Business, 2017)
This presentation is based on and continues a previous study dealing with linguistic politeness in business correspondence (Danish/French). On the basis of J.R. Searle’s theory of speech acts, H.P. Grice’s Cooperative Principle and Brown and Levinson’s politeness theory, French complimentary closes are analyzed. The paper presents a pilot study which looks at recommendations given by textbooks as well as closes in authen-tic business correspondence. The study has three aims. One aim is to establish the degree to which textbook recommendations differ, the second is to present an outline of any divergences between recommendations and linguistic behaviour as evidenced in a corpus of authentic French business correspondence. The third aim of the study is to provide the Danish correspondent with some guidelines, based on the theory of face and politeness strategies, which will hopefully permit him or her to choose complimentary closes in agreement with the conventions which seem to apply to French business cor-respondence.